Systematic review and meta-analysis of therapeutic hypothermia in animal models of spinal cord injury. - Peter E Batchelor; Peta Skeers; Ana Antonic; Taryn E Wills; David W Howells; Malcolm R Macleod; Emily S Sena (PLoS ONE)
Background Therapeutic hypothermia is a clinically useful neuroprotective therapy for cardiac arrest and neonatal hypoxic ischemic encephalopathy and may potentially be useful for the treatment of other neurological conditions including traumatic spinal cord injury (SCI). The pre-clinical studies evaluating the effectiveness of hypothermia in acute SCI broadly utilise either systemic hypothermia or cooling regional to the site of injury. The literature has not been uniformly positive with conflicting studies of varying quality, some performed decades previously. Methods In this study, we systematically review and meta-analyse the literature to determine the efficacy of systemic and regional hypothermia in traumatic SCI, the experimental conditions influencing this efficacy, and the influence of study quality on outcome. Three databases were utilised; PubMed, ISI Web of Science and Embase. Our inclusion criteria consisted of the (i) reporting of efficacy of hypothermia on functional outcome (ii) number of animals and (iii) mean outcome and variance in each group. Results Systemic hypothermia improved behavioural outcomes by 24.5% (95% CI 10.2 to 38.8) and a similar magnitude of improvement was seen across a number of high quality studies. The overall behavioural improvement with regional hypothermia was 26.2%, but the variance was wide (95% CI -3.77 to 56.2). This result may reflect a preponderance of positive low quality data, although a preferential effect of hypothermia in ischaemic models of injury may explain some of the disparate data. Sufficient heterogeneity was present between studies of regional hypothermia to reveal a number of factors potentially influencing efficacy, including depth and duration of hypothermia, animal species, and neurobehavioural assessment. However, these factors could reflect the influence of earlier lower quality literature. Conclusion Systemic hypothermia appears to be a promising potential method of treating acute SCI on the basis of meta-analysis of the pre-clinical literature and the results of high quality animal studies.